THE UTILIZATION OF ANIMATION VIDEO IN NARRATIVE TEXT WRITING CLASS: AN EXPLORATION OF STUDENTS’ PERCEPTIONS - Misbah Hayati Siregar (UIN Sumatera Utara, 2021)
The utilization of animation video as a strategy based on CALL (Computer-Assisted Language Learning) approach has been implemented by English language teachers, practitioners, and facilitators due to its enjoyable and meaningful impacts on students’ learning. This present study aimed to describe the students’ perceptions on utilizing animation video in English writing class focusing on narrative text. Qualitative research approach, particularly a case study design was employed to conduct this study. To collect the data, the researcher used questionnaire, interview, and documentation which were analyzed with descriptive statistics and Miles and Huberman theory. Twenty-eight students were recruited as the participants in this study, however only three were invited to the interview session which was conducted to deeper explore their perceptions of the animation video utilization. The results revealed that there were three main findings which tended to be positive perceptions, namely: 1) enthusiasm in the use of animation video as a learning media, 2) better comprehension of the story which helped them to portray the concept easily, to acquire more vocabulary, to organize the generic structure, and to convey the moral lesson, and 3) students felt motivated to write narrative text properly. From those results, this study concludes that the utilization of animation video in narrative text writing class has given great contributions for the students’ learning. This study suggests that the use of animation video be practiced in English language teaching learning process, particularly in the teaching and learning of narrative text writing.